Pendampingan Digitalisasi Bisnis KWT Soka Makmur - Mahendra Adhi Nugroho; Ponty Sya'banto Putra Hutama; Safiera Faradila Azzahra (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
KWT Soka Makmur faces challenges in the digital world but does not yet have sufficient skills to manage its business digitally. Thus, it is necessary to hold 1). Training and mentoring in business digitization strategies using e-commerce marketplace 2). Training and mentoring in mastering internet-based customer governance using a mobile web page. The training and mentoring activities results show an increase in KWT Soka Makmur members' capability to manage business digitally. After the mentoring activity, KWT Soka Makmur has an e-commerce marketplace account and a mobile web page for business digitization. KWT Soka Makmur management also has sufficient skills in managing businesses digitally.